Paguristes gagnaisoni Gagnaison 2012 - Ossó, Àlex; Gagnaison, Cyril; Gain, Olivier (Zenodo, 2022)
Paguristes gagnaisoni Gagnaison, 2012 (Fig. 3G-K) Paguristes gagnaisoni Gagnaison, 2012: 69-71, figs 3-5. MATERIAL EXAMINED AND MEASUREMENTS (in mm). — One complete right chela, ULB-IV-A (19): L = 6; H = 4.5; T = 3. — Two incomplete right chelae ULB-IV-A (19.2): L = 11; H = 6; T = 5.5. ULB-IV-A (17): L = 12.5; H = 7; T = 7. LOCALITY AND HORIZON. — ‘Blandinerie’ quarry, Breil (Maine-et-Loire). ‘Savignean facies’, Langhian (middle Miocene). DESCRIPTION Palm almost subtrapezoidal, slightly wider than high, thick, ovoid in section. Upper margin straight, ornated with a row of bluntly rounded granules; lower margin clearly convex, sharp-edged, armed with a row of raised tubercles, varying from blunt to pointed triangular forwardly directed giving a dentate aspect. Outer margin convex, densely covered by blunt granules of different sizes; inner margin strongly convex at the mid, smooth. Index inverted triangular in section, somewhat shorter than half the palm, gently curved inwards; outer occlusal margin with large flattened molariform teeth; inner occlusal margin with a row of smaller blunt teeth. REMARKS Paguristes gagnaisoni was the first paguroid found and described from the ‘Faluns’ (Gagnaison 2012), albeit the presence of hermit crabs was already expected, in view of the findings of gastropod shells covered by bryozoans (Lecointre 1947). It was assigned to Paguristes by its similarity with the right chela of P. santamartaensis Feldmann,Tshudy &Thomson, 1993 (Paguridae Latreille, 1802) from the Upper Cretaceous of the Antarctica.It is assumed that the studied remains belong to the major chela. The chela ULB-IV-A (17) (Fig. 3J, K), present an apparently different ornamentation in the lower half and distal part of its outer margin, formed by elongate and serrate granules, forming short terraces forward directed of squamous aspect, reminiscent of the ornamentation of some porcellanids chelae. However, this fragment of chela shows the same general features that Paguristes gagnaisoni, therefore it is tentatively left within this species. Paguristes gagnaisoni presents strong similarities such as similar outline, strongly granulate surface, and dentate lower margin of palm, with Anisopagurus leganyii Müller, 1984 (Paguridae), from the middle Miocene of the Central Paratethys (Hungary), whose fossil decapods population has great affinities with the decapod population of the ‘Faluns’. : Published as part of Ossó, Àlex, Gagnaison, Cyril & Gain, Olivier, 2022, A re-appraisal of the middle-late Miocene fossil decapod crustaceans of the ' Faluns' (Anjou-Touraine, France), pp. 207-228 in Geodiversitas 44 (6) on page 212, DOI: 10.5252/geodiversitas2022v44a6, http://zenodo.org/record/6079765 : {"references": ["GAGNAISON C. 2012. - Des bernard-l'hermites dans les faluns miocenes de Channay-sur-Lathan (Indre-et-Loire, France). Cossmanniana 14: 67 - 72.", "LECOINTRE G. 1947. - Geologie regionale de la France. 4: LaTouraine. Hermann & Cie, Paris, 240 p. (Actualites scientifiques et industrielles; 1027)", "FELDMANN R. M., TSHUDY D. M. & THOMSON M. R. A. 1993. - Late Cretaceous and Paleocene decapods crustaceans from James Ross Basin, Antarctic peninsula. The Paleontological Society, Memoire 28: 1 - 41. https: // doi. org / 10.1017 / S 0022336000062077", "LATREILLE P. A. 1802. - Histoire naturelle, generale et particuliere des Crustaces et des Insectes. Ouvrage faisant suite aux Oeuvres de Leclerc de Buffon, et Partie du Cours complet d'Histoire naturelle redige par C. S. Sonnini, Membre de plusieurs Societes savantes. F. Dufart, Paris, vol. 3: 1 - 468. https: // doi. org / 10.5962 / bhl. title. 15764", "MULLER P. 1984. - Decapod Crustacea of the Badenian. Geologica Hungarica, Series Palaeontologica 42: 25 - 317."]}